How inequality, fairness concerns, and norms affect individual behaviour - Hochleitner, Anna (2023)
This thesis consists of three self-contained chapters that study different facets of individual decision-making and show that human behaviour is strongly influenced by the social and economic environment we are interacting within. While Chapters 1 and 2 focus on the topics of social inequality and fairness concerns, Chapter 3 explores the impact of norms on behaviour.